Implementation of the Problem Based Learning Model on Critical Thinking and Problem-Solving Skills in Dynamic Electricity Material - Intan Kemala Sari NS; Nurdin Siregar; Rita Juliani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effect of problem based learning model on critical thinking ability and physics problem solving of high school students. This study is a quasi-experimental study with a two-group design with two classes, namely the experimental class and the control class. The population of this study consisted of 2 classes and sampling was carried out by saturated sampling. Class XII MIA 1 as the experimental class and class XII MIA 2 as the control class, each consisting of 30 students. The instrument used in this study was a learning outcome test in the form of an essay test of 10 questions. Data analysis was carried out using the MANOVA test. The results of the study showed that the average pretest and posttest scores in the experimental class were 57.00 and 84.00, respectively, while the average pretest and posttest scores in the control class were 53.00 and 73.50, respectively. Data analysis using the MANOVA test concluded that there was an effect of the problem based learning model on critical thinking ability and problem solving of high school students